PENGGUNAAN STRATEGI METAKOGNITIF MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Novia Pratiwi; Nana Rahayu; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The study aimed to find out how metacognitive strategies are used and see if there are differences in the use of metacognitive strategies between the three forces. This research uses descriptive methods with quantitative approaches. Respondents in this study were 98 students in the class of 2020, 2019 and 2018 of FKIP Japanese language education at Riau University. The results showed that all indicators of metacognitive strategies belonged to the high category with an average value (3.53). Based on the results of the one way anova test there is a difference in the use of metacognitive strategies between the 2020, 2019 and 2018 forces. Judging from the three metacognitive strategy indicators, it is known that the 2020 force uses its metacognitive strategy better than the 2019 and 2018 forces. Then the use of the 2019 class metacognitive strategy is better than the 2018 force.Key Words: Use of Metacognitive Strategies